A SYSTEMATIC REVIEW OF THE BENEFITS AND CHALLENGES OF ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Awal Kurnia Putra Nasution; Muhammad Hasyimsyah Batubara; Imam Munandar; Nurmalina (Jurnal Mantik, 2022)
Online learning is a learning option that is applied during the COVID-19 pandemic. Online learning has its benefits and challenges, especially during the COVID-19 pandemic, where almost all learning is done online. The purpose of this article is to map the benefits and challenges of online learning, especially those carried out during the COVID-19 pandemic. The research method used is a systematic literature review; there are 12 articles used as data sources after adjusting for inclusion and exclusion criteria. The study results show that many benefits were found for improving online learning in the future and various challenges that must be faced. One of the benefits that need attention is establishing a digital learning environment and using social media in learning. A fundamental challenge is the adaptation of learning technology. Future research is needed to build digital learning environments using social media.